Fear of Making Mistakes and its Effect on Pre-Service English Teachers’ Oral Communication Skills - Cabrera Mera, Martha Elizabeth; Dos Santos, Jardel Coutinho (Arandu UTIC, 2025)
This study investigates how pre-service English teachers' oral communication abilities are affected by their anxiety about making mistakes. Data were gathered via surveys, interviews, classroom observations, and visual narratives using an explanatory sequential mixed techniques methodology. The results show that students' confidence and willingness to participate in oral activities are greatly impacted by their fear of making mistakes, which can result in anxiety, mental blocks, and avoidance strategies. Peer and instructor presence was found to be a significant contributing element to this fear, as students feared being mocked or criticized. As a result, they had fewer possibilities for practice and development because their speaking abilities were hindered. The study emphasizes the necessity of a supportive classroom setting where errors are accepted as a necessary learning component. Promoting group projects and scaffolding methods. Promoting teamwork and using scaffolding strategies would help pre-service teachers become more confident and improve their oral communication abilities. The results highlight the significance of addressing anxiety in teacher preparation programs and advance our understanding of emotional barriers in language acquisition.